2010
DOI: 10.1097/bth.0b013e3181dfbcb1
|View full text |Cite
|
Sign up to set email alerts
|

Use of 2 Column Screws to Treat Transcondylar Distal Humeral Fractures in Geriatric Patients

Abstract: We describe fixation of transcondylar distal humeral fractures with column screws in geriatric patients and review our initial results. We conducted a retrospective review of a prospectively collected database at a Level I trauma center. Six patients met inclusion criteria of age older than 65 years and treatment of minimally or nondisplaced transcondylar distal humeral fracture with column screws only. All were closed fractures with no associated nerve injuries. One patient was lost to follow-up. The mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Similar results were obtained by Vala P et al [13] in their study. Our complication rates were also comparable with other studies in literature [12,14] .…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were obtained by Vala P et al [13] in their study. Our complication rates were also comparable with other studies in literature [12,14] .…”
Section: Discussionsupporting
confidence: 91%
“…Satisfactory fixation with 2 cannulated screws, applied in a crisscross manner in older patients with transcondylar fractures, has also been reported. 6,7 In our study, union was achieved in 2 patients in group A who were treated with crisscross fixation. This technique must be carefully used in older patients with minimally displaced or undisplaced low transcondylar fractures with longer immobilization.…”
Section: Discussionmentioning
confidence: 52%
“…A crisscross screw fixation method was introduced for transcondylar distal humeral fractures. 9 , 10 They reported that this method was good to save operation time, and they achieved bony union in all cases. However, the union time was on average 7.2 weeks to 3 months and there was screw loosening in some patients, whereas the mean union time was 5.3 weeks in this study.…”
Section: Discussionmentioning
confidence: 94%
“…It is reported that most transcondylar humeral fractures occur in older patients after low-energy injuries. 10 , 12 , 18 Therefore, healing of geriatric fractures can be ensured not only by a stable construct of the surgery but also by biologic factors. 18 The transcondylar area is thought to be prone to fractures because the bones in that region of the body are relatively thin.…”
Section: Discussionmentioning
confidence: 99%